Cost Manipulation Incentives under Cost Reimbursement: Pension Costs for Defense Contracts - Thomas, Jacob K.; Tung, Samuel (The Accounting Review, 1992)
[This article examines the incentives for defense contractors that operate under cost reimbursement to manipulate pension costs. We investigate pension costs because of their high discretionary component and their importance to managers seeking to manipulate costs. For example, two of the 20 standards issued by the Cost Accounting Standards Board (CASB) focus exclusively on the determination of allowable pension costs. Also, the availability of detailed data on pension funding and actuarial variables across plans sponsored by the same firm and across plans of different firms allows for extensive tests of the hypothesized effects of cost reimbursement. Defense contractors are selected because they are closely associated with cost reimbursement (see, e.g., Chwastiak 1990; Pownall 1986), and the terms "defense" and "non-defense" are used here to denote the presence and absence, respectively, of reimbursed costs. The analysis suggests that overfunding is valuable to defense contractors only if they also have or plan to have non-defense business. Two generic funding strategies are described: across-time and across-contract. In both cases, plans are overfunded when employees work on defense contracts, then these excess pension assets are withdrawn when the employees work on non-defense business. The across-contract strategy is implemented by transferring employees and associated pension assets and liabilities between defense and non-defense plans. The across-time strategy is implemented by having individual plans alternate between extended periods wherein they first cover defense contracts, then cover non-defense business. The firm can achieve this effect either by selectively "cycling" defense contracts across plans or by changing its proportion of defense contracts over time. Evidence of inter- and intra-firm variation in funding levels and actuarial variables is presented for a sample of 80 major defense contractors. Across firms, funding levels increase with the proportion of defense revenues, reach a peak when defense revenues equal non-defense revenues, and then decrease as the proportion of defense revenues increases (an inverted-U-shaped relation). This last downward sloping portion of the relation is consistent with the across-contract strategy as it indicates reduced ability to make transfers as the pool of non-defense employees declines. Although evidence of such transfers between defense and non-defense plans could not be obtained, indirect support for this view is provided at the intra-firm level. Relative to a control sample, defense contractors sponsor more plans (which is consistent with their having separate plans for defense and non-defense activities) and exhibit a wider range of funding levels and actuarial variables across plans sponsored by each firm (which is consistent with differential funding of the two groups of plans). Two important features regarding the scope of this study are worth noting. First, cost reimbursement could also create incentives to inflate pension costs by increasing the level of promised pension benefits (more generous benefits), or by using various allocation strategies, whereby more common pension costs are allocated to defense contracts. Although we are unable to investigate these incentives due to data limitations, our inter- and intra-firm results are not confounded by these effects. Second, our results do not prove systematic "overcharging," as competition among suppliers and the ability of customers to identify and adjust for unusually high pension costs are not examined.]